2009
DOI: 10.1016/j.ejps.2009.02.008
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 targeting of doxorubicin-loaded PLGA nanoparticles to lung epithelial cells

Abstract: Interaction of leukocyte function associated antigen-1 (LFA-1) on T-lymphoctytes and intercellular adhesion molecule-1 (ICAM-1) on epithelial cells controls leukocyte adhesion, spreading, and extravasation. This process plays an important role in leukocyte recruitment to a specific site of inflammation and has been indentified as a biomarker for certain types of carcinomas. Cyclo-(1,12)-PenITDGEATDSGC (cLABL) has been shown to inhibit LFA-1 and ICAM-1 interaction via binding to ICAM-1. In addition, cLABL has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 41 publications
10
126
2
Order By: Relevance
“…Higher uptake of targeted nanoparticles by SKBR3 cells was in agreement with a previous study. 26 These results also suggest that immunonanoparticles may be taken up more rapidly than nontargeted nanoparticles.…”
Section: In Vitro Docetaxel Releasesupporting
confidence: 54%
“…Higher uptake of targeted nanoparticles by SKBR3 cells was in agreement with a previous study. 26 These results also suggest that immunonanoparticles may be taken up more rapidly than nontargeted nanoparticles.…”
Section: In Vitro Docetaxel Releasesupporting
confidence: 54%
“…In this study, the cytotoxicity of four different treatments (IDNP w/o laser treatment, AIDNP w/o laser treatment, IDNP w/ laser treatment and AIDNP w/ laser treatment) were investigated. Cells were seeded into a 96-well plate on the first day, and after overnight incubation they were exposed to different treatments The slow sustained release of DOX from targeted AIDNP and the biphasic behavior of the release profile observed in both AIDNP and IDNP are consistent with other literature reports as well (Yang 2007;Chittasupho 2009;. The two phases of DOX release correspond to an initial burst release, followed by a sustained slow release.…”
Section: Introductionsupporting
confidence: 71%
“…ICAM-1 was selected based on: (a) its presence on GI epithelial cells 35,36 and overexpression under GI pathology; [36][37][38][39] (b) its ability to mediate binding and endocytosis of drug conjugates and carriers; 46 and (c) prior literature on ICAM-1-targeting in cell culture and in vivo. [41][42][43][44]47 We utilized model polystyrene NCs since: (a) polymer-based carriers are stable in the GI environment compared to other formulations; 7,33 Cross-sectional dissections were made in the stomach, duodenum, jejunum, and ileum. Notes: Dissected tissue was thoroughly rinsed to remove unbound NCs and imaged by microscopy to detect tissue-associated fluorescent NCs.…”
Section: Discussionmentioning
confidence: 99%
“…39 We and others have shown that, upon intravenous administration in animal models, ICAM-1 targeting improves biodistribution of diagnostic and therapeutic agents. [40][41][42][43][44] Furthermore, ICAM-1-targeting NCs can be modulated to display optimal antibody surface density, size, and shape, leading to internalization into cells, which is suitable for intracellular drug transport. [45][46][47] In the context of drug delivery in the GI tract, however, ICAM-1 targeting has not been explored.…”
Section: Introductionmentioning
confidence: 99%